Soil carbon in the Nationally Determinted Contributions: Analysis results - Wiese-Rozanova, Liesl D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presentation by Liesl Wiese-Rozanova, International agricultural science and policy consultant, South Africa. The presentation was part of the Webinar on Soil carbon in the Nationally Determined Contributions hosted by CCAFS, the German Ministry of Food and Agriculture, and the 4 Per Mille Initiative and held on Earth Day, 22 April 2020.